Investigating recent audit reform in the Australian context: An analysis of the KAM disclosures in audit reports 2017–2018. Issue 3 (14th September 2020) - Kend, Michael; Nguyen, Lan Anh
Abstract : The aim of this study is to explore the new Australian auditing regulations around Key Audit Matters (KAMs), fully adopted since 2017, by reporting on matters published in over 3, 000 Australian statutory audit reports from 2017 to and including 2018 reports. The study provides the first evidence on whether auditors used the same or different disclosures related to audit procedures when reporting on the same KAM in the second year in Australia. The findings suggest the most common KAM disclosures are related to "impairments of goodwill and intangible assets, " "revenue recognition, " "asset valuation, " "acquisitions, " and "exploration and evaluation." Around 70% of Australian auditees had the same KAMs disclosed in both years 2017 and 2018. The study found differences between large and small audit practitioners related to the average number of KAMs disclosed and the average number of audit procedures undertaken per KAM. There were also differences found between industries and auditee size.